States of war since 9/11 : Terrorism, sovereignty and the War on Terror - Houen, Alex (Abingdon, Oxon : Routledge, 2014)
'This multidisciplinary edited volume explores how the spread of the'War on Terror' has entwined matters of state sovereignty and states of war into mutually-affecting relations. Pre-emptive attacks on terrorist groups in'rogue' states;'outsourcing' of state militancy; and the mutable state of armed conflict required to wage a'hybrid war' have increasingly been issues for the'War on Terrorism' (WoT). Taken together, they also provide just one example of how any detailed exploration of the states involved needs to address not only matters of nation-state sovereignty, but also the modes (states) of militancy that the War on Terror has assumed in spreading internationally. Moreover, such measures have seen the spread of the War on Terror to countries such as Israel, Russia, Ethiopia, and Uganda, all of whom have justified their own attacks in other nation-states as a war of'self defence' against terrorism. And as the War on Terror has spread with the willingness of other countries to adopt it, those countries have in turn adapted emergency modes of war-- including targeted assassinations, indefinite detention, rendition, and torture. This work relates legal and political aspects of the War on Terror and also incorporates a'war and society approach' in order to examine how society has effected changes in war, and how war and militarization have assumed various states in society. Doing so allows for consideration of how different'states' have become interconnected in the War on Terror-- including states of warfare and national governance, and those of social affect. Part I offers a series of framing chapters that take a broad view of particular issues; After the framing chapters of Part One, the chapters in Part II examine how modes (states) of the War on Terror have spread as a result of being taken up in various nation-states. In relating various states of war and wars against states, this volume will be a significant and novel contribution to critical study of the War on Terror. While most other studies of it have limited their purview to a principal cast of nation-states (USA, UK, Iraq, Afghanistan), this volume focuses on ways in which the War on Terror has proliferated beyond those states. And whereas most other studies have limited their analysis of the modes of war to a particular perspective (e.g., international law, security, or development), this volume addresses how those modes have ramified and thus assumed various states in the process of being spread. This book will be of much interest to students of critical terrorism studies, '--
Includes bibliographical references and index.
Keywords: War on Terrorism, 2001-2009.; War on Terrorism, 2001-2009 -- Political aspects; Terrorism; Sovereignty; Sovereignty, Violation of